1995
DOI: 10.1177/197140099500800637
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Postprocedural Hypotension following Carotid Artery Stenting

Abstract: This study is performed to investigate risk factors of hypotension in response to elective carotid stenting. Forty-four lesions of 40 consecutive patients (mean age 70.4 ± 8.2 years) were retrospectively analyzed. Easy Wall stent was applied in 15 lesions and SMART stent in 29 lesions. We investigated correlations between the occurrence rate of postoperative hypotension below 90 mmHg and persisting over three hours and findings of preoperative angiograms, ultrasonograms and clinical characteristics. Postproced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…21 This wide variation is primarily a consequence of inconsistency in the definition of PPH. 24,2831 This study demonstrated significant associations between the development of PPH and severe lesion calcification, specific EPDs and stents, and contrast volume on univariable analysis. Both the contrast volume and stent type were independent predictors of PPH.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…21 This wide variation is primarily a consequence of inconsistency in the definition of PPH. 24,2831 This study demonstrated significant associations between the development of PPH and severe lesion calcification, specific EPDs and stents, and contrast volume on univariable analysis. Both the contrast volume and stent type were independent predictors of PPH.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, Nonaka et al 31 have also demonstrated that shorter stents generate greater radial force than do longer stents of the same design and diameter. This is an important observation because lesions close to the carotid bifurcation (<10 mm) are implicated in hemodynamic instability 41 and are more likely to have been treated with shorter stents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that 5–47% of patients undergoing CAS may develop hemodynamic complications [ 5 9 ]. Asymptomatic stenosis, stenosis proximity to bifurcation, calcification at the bifurcation, eccentric stenosis, and dilation percentage may predict the risk of hemodynamic complications of CAS [ 10 , 11 ]. Post-CAS hypotension correlates with higher risk of stroke/transient ischemic attack (TIA), myocardial infarction (MI), prolonged hospital stay (> 1 day), and in-hospital mortality [ 12 ]⁠.…”
Section: Introductionmentioning
confidence: 99%